Analisis Usahatani Jeruk Siam (Citrus nobilis Tan) (Studi Kasus Usahatani H. Hairul) di Kelurahan Sungai Bamban Kecamatan Rantau Badauh Barito Kuala - Herliani Herliani; Artahnan Aid; Muhammad Husaini (Universitas Lambung Mangkurat, 2015)
Recently, the fruit demand has increasedin accordance with population growth, improving living standards and income, public awareness of nutrition, and development of industry and tourism sectors. The study explores the agribusiness activity, financial feasibility, and product distribution in the study site. The study calculates that the investment indicatorsof RCR is 4. 72 (> 1 ), the NPV is/DR 322,651,911.79 (> 0), Net BIG is 3.90 (> 1), and /RR is 25.18% (> 20%). Thus, it can be conclude that the citrus farming is financially feasible. The orange distributed in village through direct purchases. Then it is sold to the market or other island cities such as Surabaya end Bali. Finally, some of the oranges are processed further into canned food, beverages and other processed food.